Gereja sebagai Komunitas yang Sehat dan Dampaknya bagi Orang Percaya - Iman Pasrah Zai; Yeremia Hia (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
As a community of believers, the church plays an important role in shaping the faith and character of Christians. A healthy church is marked by the growth of its congregation and the spiritual vitality of its members. The purpose of this study is to identify the characteristics of a healthy church and evaluate how these traits impact the strengthening of believers' faith. Using a qualitative-descriptive approach and theological literature research, it was found that a healthy church possesses characteristics such as sound biblical teaching, genuine love for the congregation, servant leadership, active involvement of members according to the gifts of the Holy Spirit, and a strong commitment to prayer and fellowship. For believers, a healthy church fosters dynamic spiritual growth, harmonious community life, and active participation in ministry and evangelism. Such churches are not merely places of worship; they also act as agents of real social transformation. Therefore, a well-functioning church will produce resilient, loving Christians who serve as a light to others.